Ten‐year immune persistence and safety of the HPV‐16/18 AS04‐adjuvanted vaccine in females vaccinated at 15–55 years of age - Schwarz, Tino F.; Galaj, Andrzej; Spaczynski, Marek; Wysocki, Jacek; Kaufmann, Andreas M.; Poncelet, Sylviane; Suryakiran, Pemmaraju V.; Folschweiller, Nicolas; Thomas, Florence; Lin, Lan; Struyf, Frank (Cancer medicine (Malden, MA), 2017)
Women remain at risk of human papillomavirus (HPV) infection for most of their lives. The duration of protection against HPV‐16/18 from prophylactic vaccination remains unknown. We investigated the 10‐year immune response and long‐term safety profile of the HPV‐16/18 AS04‐adjuvanted vaccine (AS04‐HPV‐16/18 vaccine) in females aged between 15 and 55 years at first vaccination. Females who received primary vaccination with three doses of AS04‐HPV‐16/18 vaccine in the primary phase‐III study (NCT00196937) were invited to attend annual evaluations for long‐term immunogenicity and safety. Anti‐HPV‐16/18 antibodies in serum and cervico‐vaginal secretions (CVS) were measured using enzyme‐linked immunosorbent assay (ELISA). Serious adverse events (SAEs) were recorded throughout the follow‐up period. Seropositivity rates for anti‐HPV‐16 remained high (≥96.3%) in all age groups 10 years after first vaccination. It was found that 99.2% of 15–25‐year olds remained seropositive for anti‐HPV‐18 compared to 93.7% and 83.8% of 26–45‐year olds and 45–55‐year olds, respectively. Geometric mean titers (GMT) remained above natural infection levels in all age groups. Anti‐HPV‐16 and anti‐HPV‐18 titers were at least 5.3‐fold and 3.1‐fold higher than titers observed after natural infection, respectively, and were predicted to persist above natural infection levels for ≥30 years in all age groups. At Year 10, anti‐HPV‐16/18 antibody titers in subjects aged 15–25 years remained above plateau levels observed in previous studies. Correlation coefficients for antibody titers in serum and CVS were 0.64 (anti‐HPV‐16) and 0.38 (anti‐HPV‐18). This study concluded that vaccinated females aged 15–55 years elicited sustained immunogenicity with an acceptable safety profile up to 10 years after primary vaccination, suggesting long‐term protection against HPV. The HPV‐16/18 AS04‐adjuvanted vaccine produced a sustained immune response in women aged 15–55 years at vaccination for up to 10 years, with an acceptable safety profile. Study results suggest that women in age groups not targeted by adolescent immunization and catch‐up programs may still individually benefit from HPV vaccination.